Prevalence and Characterization of Biallelic and Monoallelic NTHL1 and MSH3 Variant Carriers From a Pan-Cancer Patient Population. (2021) - Salo-Mullen, Erin E.; Maio, Anna; Mukherjee, Semanti; Bandlamudi, Chaitanya; Shia, Jinru; Kemel, Yelena; Cadoo, Karen A.; Liu, Ying; Carlo, Maria; Ranganathan, Megha; Kane, Sarah; Srinivasan, Preethi; et al.
Abstract : PURPOSE: NTHL1 and MSH3 have been implicated as autosomal recessive cancer predisposition genes. Although individuals with biallelic NTHL1 and MSH3 pathogenic variants (PVs) have increased cancer and polyposis risk, risks for monoallelic carriers are uncertain. We sought to assess the prevalence and characterize NTHL1 and MSH3 from a large pan-cancer patient population. MATERIALS AND METHODS: Patients with pan-cancer (n = 11, 081) underwent matched tumor-normal sequencing with consent for germline analysis. Medical records and tumors were reviewed and analyzed. Prevalence of PVs was compared with reference controls (Genome Aggregation Database). RESULTS: NTHL1 -PVs were identified in 40 patients including 39 monoallelic carriers (39/11, 081 = 0.35%) and one with biallelic variants (1/11, 081 = 0.009%) and a diagnosis of isolated early-onset breast cancer. NTHL1 -associated mutational signature 30 was identified in the tumors of the biallelic patient and two carriers. Colonic polyposis was not identified in any NTHL1 patient. MSH3 -PVs were identified in 13 patients, including 12 monoallelic carriers (12/11, 081 = 0.11%) and one with biallelic MSH3 variants (1/11, 081 = 0.009%) and diagnoses of later-onset cancers, attenuated polyposis, and abnormal MSH3-protein expression. Of the 12 MSH3 carriers, two had early-onset cancer diagnoses with tumor loss of heterozygosity of the wild-type MSH3 allele. Ancestry-specific burden tests demonstrated that NTHL1 and MSH3 prevalence was not significantly different in this pan-cancer population versus controls. CONCLUSION: NTHL1 and MSH3 germline alterations were not enriched in this pan-cancer patient population. However, tumor-specific findings, such as mutational signature 30 and loss of heterozygosity of the wild-type allele, suggest the potential contribution of monoallelic variants to tumorigenesis in a subset of patients.